Identifying and Analyzing Stratums in Virtual Reality Geological Environment: A Three-Dimensional Approach (International Journal of Food and Nutritional Sciences, 2022)
The research of a high-technology measure for geologists using virtual reality (VR) technology hasenabled the representation of geological data in both static and dynamic formats. This study proposesa three-dimensional approach for identifying and analyzing stratums in VR geological environments,consisting of three steps: pretreating geological data, constructing three-dimensional stratum models,and visually analyzing and correcting space. These steps are verified and detected using a spaceinformation quality detecting model.